In one person : a novel - Irving, John, 1942- (Simon & Schuster, 2012)
The author's most political novel since The Cider House Rules and A Prayer for Owen Meany, this novel is an intimate and unforgettable portrait of the solitariness of a bisexual man who is dedicated to making himself "worthwhile."